The effects of dendritic cell-based vaccines in the tumor microenvironment: Impact on myeloid-derived suppressor cells - Sánchez-León, María Luisa; Jiménez-Cortegana, Carlos; Cabrera, Gabriel; Vermeulen, Elba Mónica; de la Cruz-Merino, Luis; Sánchez-Margalet, Victor (Frontiers in Immunology, 2022)
Dendritic cells (DCs) are a heterogenous population of professional antigen presenting cells whose main role is diminished in a variety of malignancies, including cancer, leading to ineffective immune responses. Those mechanisms are inhibited due to the immunosuppressive conditions found in the tumor microenvironment (TME), where myeloid-derived suppressor cells (MDSCs), a heterogeneous population of immature myeloid cells known to play a key role in tumor immunoevasion by inhibiting T-cell responses, are extremely accumulated. In addition, it has been demonstrated that MDSCs not only suppress DC functions, but also their maturation and development within the myeloid linage. Considering that an increased number of DCs as well as the improvement in their functions boost antitumor immunity, DC-based vaccines were developed two decades ago, and promising results have been obtained throughout these years. Therefore, the remodeling of the TME promoted by DC vaccination has also been explored. In this chapter, we aim to review the effectiveness of different DCs-based vaccines in murine models and cancer patients, either alone or synergistically combined with other treatments, being especially focused on their effect on the MDSC population.